Closure Type Effects on the Structural Pattern of an Inverted Extensional Basin of Variable Width: Results from Analogue Models - Jara-Munoz, P (Elsevier Ltd, 2018)
In order to further understand the controls on the structural configuration of inverted basins, previous research has vastly explored the role of rift-stage stress field variations on the resulting structure produced by basin inversion. Analogue modeling has broadly enabled geoscientists to gain insight into the controls on the structural evolution during basin inversion, such as: the inherited structural array of the basin, sedimentary load or sedimentary thickness, plan-view shape of the basin (length and width), and variations on the governing stress field, among other factors. This work sheds light on the influence exerted by the closure style on inversion of an elongated model basin with a variable width, generated by differential extension. We subsequently induced inversion by modifying the orientation of the post-rift contractional stress field: (i) in a first model, contraction is homogeneous along-strike (parallel to the major axis of the basin); and (ii) in a second model, contraction is heterogeneous along-strike and exerted in the same orientation and amount in which extension was induced (about a pivot point). We focus on the three-dimensional geometry of the structures generated by inversion, their vergence and surficial trace, and where they are prone to concentrate within the basin, to finally analyze and compare our results with natural examples of inverted Andean basin systems. Our results indicate that most of the contractional deformation imposed in the analog models is absorbed in the interiors of the basin in its widest zones by means of inverted normal faults and backthrusts. However, when the amount of shortening is higher than extension, deformation is propagated outside the basin where shortcuts and new oblique reverse faults are dominant, which promote a major uplift. © 2017 Elsevier Ltd
Keywords: Analogue modeling; Tectonic inversion; Basin width; Closure style